Hard disk drive with built-in thin substrate and bottom plate member for hard disk drive with built-in thin substrate

By introducing specific metallographic structure into the aluminum alloy base plate of the hard disk drive, the problem of the hard disk drive's impact resistance decreases after the disk becomes thinner, achieving higher impact resistance and disk stability.

CN116391053BActive Publication Date: 2025-02-18UACJ CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180070000.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-22
Filing Date
2021-10-07
Publication Date
2025-02-18
Estimated Expiration
2041-10-07

AI Technical Summary

Technical Problem

Existing hard drives have challenges in improving impact resistance, especially when the disk becomes thinner.

Method used

By introducing metallographic structure into the aluminum alloy base plate with a built-in hard disk drive of a thin substrate, it is ensured that the circumference of the second phase particles with a maximum diameter of 10 μm or more reaches 3mm/mm2 or more, and the second phase particles with a maximum diameter of 500 μm or more are 0 pixels/mm2, thereby improving the impact resistance of the disk.

Benefits of technology

This technology effectively improves the impact resistance of the disk, reduces the impact of the impact on the disk, and prevents the disk from deformation and damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116391053B_ABST
    Figure CN116391053B_ABST
Patent Text Reader

Abstract

The present invention relates to a hard disk drive (1) with a thin substrate, comprising: a disk-shaped magnetic disk (30) having a through hole in the center; a spindle motor (20) inserted into the through hole of the magnetic disk (30) and supporting the magnetic disk (30) in a manner that allows co-rotation; and a base plate (10) made of aluminum alloy for supporting the spindle motor (20). The base plate (10) has a metallographic structure, in which the circumference of the second phase particles with a maximum diameter of 10 μm or more is 3 mm / mm. 2 The number of second phase particles with a maximum diameter of 500 μm or more is 0 / mm 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hard disk drive with a built-in thin substrate and a base plate member for the hard disk drive with a built-in thin substrate. Background Art

[0002] In recent years, hard disk drives (hereinafter also referred to as "HDDs") have been widely used as recording devices for computers. A disk drive device is mounted on the HDD to support and rotate a disk for recording a medium. The disk drive device generally has one or more disks for recording data, a spindle motor for rotating the disks, and a clamping member for fixing the inner diameter side of the disks. In addition to such a disk drive device, the HDD also includes a magnetic head for processing data on each disk, an actuator for supporting the magnetic head so that it can move freely relative to the disk, and a swing arm for rotating and positioning the actuator.

[0003] However, in recent years, due to the needs of multimedia, HDDs are required to have large capacity and high density. In addition, in order to further increase the capacity, the number of disks mounted in the storage device increases, and the disks are also required to be thinner. However, if the disks are thinned, there is a problem of reduced rigidity. If the rigidity is reduced, the impact resistance used to indicate the degree to which the disk is difficult to deform is reduced, so it is required to improve the impact resistance.

[0004] In view of such actual conditions, magnetic disks with high rigidity have been strongly desired in recent years, and research has been conducted. For example, Patent Document 1 proposes a method of improving impact resistance by making an aluminum alloy substrate for a magnetic disk contain a large amount of Si that contributes to improving rigidity.

[0005] However, the method disclosed in Patent Document 1 of increasing the Si content to improve rigidity is effective in improving impact resistance, but the amount of Si that can be added is limited due to the compromise between manufacturability, and the desired good impact resistance has not been achieved at present.

[0006] (Prior art literature)

[0007] (Patent Document)

[0008] Patent Document 1: International Publication No. 2016 / 068293 Summary of the invention

[0009] Problems to be solved by the invention

[0010] The present invention has been made in view of the above-mentioned actual situation, and provides a hard disk drive with built-in thin substrate and a bottom plate member for the hard disk drive with built-in thin substrate having excellent impact resistance.

[0011] Methods for solving problems

[0012] The inventors of the present invention have conducted in-depth research on the above-mentioned problems and found that by clarifying the correlation between the disk and the base plate in a thin substrate built-in hard disk drive, it is possible to provide a thin substrate built-in hard disk drive and a base plate component for a thin substrate built-in hard disk drive that can improve the impact resistance of the disk.

[0013] One embodiment of the present invention is a hard disk drive with a built-in thin substrate, comprising: a disk-shaped magnetic disk having a through hole in the center; a spindle motor inserted into the through hole of the magnetic disk and supporting the magnetic disk in a manner that the magnetic disk can rotate together; and a bottom plate made of an aluminum alloy for supporting the spindle motor, the bottom plate having a metallographic structure, in which the circumference of second phase particles having a longest diameter of 10 μm or more is 3 mm / mm 2 The number of second phase particles with a maximum diameter of 500 μm or more is 0 / mm 2 .

[0014] Another embodiment of the present invention is a bottom plate member for a hard disk drive built in a thin substrate made of aluminum alloy, wherein the bottom plate member has a metallographic structure, and the perimeter of the second phase particles with the longest diameter of 10 μm or more in the metallographic structure is 3 mm / mm 2 The number of second phase particles with a maximum diameter of 500 μm or more is 0 / mm 2 .

[0015] Effects of the Invention

[0016] According to the present invention, there can be provided a thin substrate built-in hard disk drive, comprising: a disk-shaped magnetic disk having a through hole in the center; a spindle motor inserted into the through hole of the magnetic disk and supporting the magnetic disk in a manner that the magnetic disk can rotate together; and a base plate made of aluminum alloy for supporting the spindle motor, wherein the base plate has a metallographic structure, and the circumference of the second phase particles with a maximum diameter of 10 μm or more in the metallographic structure is 3 mm / mm 2 The number of second phase particles with a maximum diameter of 500 μm or more is 0 / mm 2 , thereby improving the impact resistance of the disk.

[0017] In addition, a bottom plate member for a hard disk drive built in a thin substrate can be provided, wherein the bottom plate member for a hard disk drive built in a thin substrate made of an aluminum alloy has a metallographic structure, and the circumference of the second phase particles with a longest diameter of 10 μm or more in the metallographic structure is 3 mm / mm 2 The number of second phase particles with a maximum diameter of 500 μm or more is 0 / mm 2 , thereby improving the impact resistance of the disk. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram showing an example of a thin substrate-built-in hard disk drive according to the present embodiment.

[0019] Figure 2 Indicates that the circumference of the second phase particles with the longest diameter of 10μm or more is 3mm / mm 2 Above the base plate and the circumference is less than 3mm / mm 2 The relationship between the time and the displacement of the substrate (disk) when the bottom plate is subjected to an impact test.

[0020] Figure 3 It is a schematic diagram showing the circumference and the longest diameter of the second phase particles.

[0021] Figure 4 It is a schematic diagram showing the area where the thickness of the bottom plate (bottom plate member) is measured.

[0022] Figure 5 This is an example of an image of the metallographic structure of a base plate taken using an optical microscope. DETAILED DESCRIPTION

[0023] Hereinafter, a hard disk drive built in a thin substrate and a base member for a hard disk drive built in a thin substrate according to the present embodiment will be described with reference to the drawings.

[0024] Figure 1 FIG. 2 is a schematic diagram showing an example of a thin substrate built-in hard disk drive according to the present embodiment. Figure 1 As shown, the thin substrate built-in hard disk drive 1 of this embodiment includes: a disk-shaped magnetic disk 30 having a through hole in the center; a spindle motor 20, which is inserted into the through hole of the magnetic disk 30 and supports the magnetic disk 30 in a manner that can rotate together; and a base plate 10 made of aluminum alloy, which is used to support the spindle motor 20. The thin substrate built-in HDD 1 further includes: a magnetic head 50, which is used to process data on the magnetic disk 30; a swing arm 70, which supports the magnetic head 50 so that it can move freely relative to the magnetic disk 30; and an actuator 40, which is used to rotate and position the swing arm 70. The magnetic disk 30 can be one or more. In addition, by combining the base plate 10 with the cover plate 60, various components such as the magnetic disk 30 are protected.

[0025] A. Aluminum alloy base plate (base plate member)

[0026] The metallographic structure of the bottom plate (bottom plate member) made of aluminum alloy will be described. It should be noted that in the following description, the structure and characteristics of the bottom plate also apply to the bottom plate member.

[0027] (Perimeter of second phase particles with the longest diameter of 10 μm or more)

[0028] In the metallographic structure of the bottom plate made of aluminum alloy, there are intermetallic compounds, particles, etc. as second phase particles. Specifically, the bottom plate has a circumference of 3 mm / mm for the second phase particles with a maximum diameter of 10 μm or more. 2 In the metallographic structure of the bottom plate, the circumference of the second phase particles with the longest diameter of 10μm or more is 3mm / mm 2 As a result, the impact resistance of the base plate is improved. It is believed that this is because the vibration energy during impact is absorbed at the interface between the second phase particles and the aluminum alloy matrix. Therefore, when the HDD is impacted, the impact is mitigated by the base plate due to the high impact resistance of the base plate, and the impact transmitted to the magnetic disk becomes smaller. As a result, the impact resistance of the magnetic disk is improved, and the deformation of the magnetic disk can be suppressed.

[0029] On the other hand, in the metallographic structure of the bottom plate, the perimeter of the second phase particles with the longest diameter of 10 μm or more is less than 3 mm / mm. 2 In the case of , the vibration energy absorbed at the interface between the second phase particles and the aluminum alloy matrix is ​​small, so the impact resistance will not be improved. Therefore, the circumference of the second phase particles existing in the metallographic structure of the bottom plate is 3mm / mm 2 The above range is preferably 5mm / mm 2 It should be noted that the upper limit of the circumference is not particularly limited, but considering the alloy composition of the bottom plate, it is preferably 1000 mm / mm 2 In addition, since the second phase particles having the longest diameter less than 10 μm hardly affect the impact resistance, the lower limit of the longest diameter of the second phase particles is less than 10 μm.

[0030] Figure 2 Indicates that the circumference of the second phase particles with the longest diameter of 10μm or more is 3mm / mm 2 Above the base plate and the circumference is less than 3mm / mm 2 The relationship between the time and displacement of the base plate (disk) during the impact test. Figure 2 As shown, it can be seen that the metallographic structure contains a circumference less than 3mm / mm 2 Compared with the bottom plate of the second phase particles with the longest diameter of 10μm or more, the metallographic structure contains a circumference of 3mm / mm 2 The maximum displacement, i.e., deformation, of the substrate (disk) is small. 2 By forming the bottom plate of the second phase particles with the longest diameter of 10 μm or more, the shock transmitted to the magnetic disk can be reduced, thereby improving the shock resistance of the magnetic disk.

[0031] Second phase particles mainly refer to precipitates and crystals of intermetallic compounds. Specifically, Al 3 Fe、Al 6 Fe、Al 6 Al-Fe intermetallic compounds such as (Fe, Mn), Al-Fe-Si, Al-Fe-Mn-Si, Al-Fe-Ni, and Al-Cu-Fe. In addition to Al-Fe intermetallic compounds, Mg-Si intermetallic compounds (Mg 2 Si, etc.), Al-Mn intermetallic compounds (Al 6 Mn, Al-Mn-Si, etc.), Al-Ni intermetallic compounds (Al 3 Ni, etc.), Al-Cu intermetallic compounds (Al 2 Cu, etc.), Al-Cr intermetallic compounds (Al 7 Cr, etc.), Al-Zr intermetallic compounds (Al 3 Zr, etc.), and the second phase particles also include Si particles, etc.

[0032] (Second phase particles with a maximum diameter of 500 μm or more)

[0033] The number of second phase particles with the longest diameter of 500 μm or more on the bottom plate is 0 / mm 2 Metallographic structure. As mentioned above, although research is being conducted to reduce the thickness of the magnetic disk and increase the number of disks that can be mounted in order to achieve a larger capacity of the HDD, the thickness of the base plate also tends to be thinner in order to increase the number of magnetic disks that can be mounted. In the case where the thickness of the base plate is thin, if coarse second phase particles (more than 500 μm) exist in the metallographic structure of the base plate, cracks or holes may occur from these starting points. In this case, the impact resistance of the base plate is reduced, and as a result, it is believed that the impact resistance of the magnetic disk is also reduced. In addition, when cracks or holes occur in the base plate, helium and the like sealed in the HDD may leak out. Therefore, there is 1 / mm in the metallographic structure. 2 The base plate with coarse second phase particles with a maximum diameter of 500 μm or more is not suitable for use as a base plate for HDD. From this point of view, it is believed that the metallographic structure of the base plate has no second phase particles with a maximum diameter of 500 μm or more per mm. 2 , thereby improving the impact resistance of the disk. It should be noted that, although the upper limit of the longest diameter of 500 μm or more is not particularly limited, it is naturally determined by the alloy composition, etc., and is about 3000 μm. In addition, the unit number / mm of the second phase particles with a longest diameter of 500 μm or more is 2 It refers to the presence of 1mm 2 The number of second phase particles with the longest diameter of 500 μm or more.

[0034] The longest diameter of the second phase particles in the metallographic structure of the bottom plate is Figure 3 As shown in FIG. , the second phase particles A are measured from a plane image observed under an optical microscope. Specifically, Figure 3 As shown, in the second phase particle A, first, the straight-line distance between a point on the contour line of the observed second phase particle A and another point on the contour line is measured. Then, the straight-line distance is measured for all points on the contour line, and finally, the largest diameter is selected from all these straight-line distances as the longest diameter. The largest diameter thus selected is defined as the longest diameter D of the second phase particle. max In addition, the perimeter of the second phase particle is, Figure 3 As shown, in the plane image of the second phase particle A observed under an optical microscope, the length L on the contour line of the observed intermetallic compound A is s It should be noted that the unit of circumference is mm / mm 2 It refers to the presence of 1mm 2 The sum of the circumferences of all second-phase particles with the longest diameter of 10 μm or more in the image. In addition, in the observation using an optical microscope, the image was taken without using a polarizing filter. The distinction between the second-phase particles and the matrix is ​​achieved by the depth of contrast in the image taken with an optical microscope, such as Figure 5 As shown, particles with a contrast darker or lighter than the matrix are regarded as second phase particles.

[0035] In addition to observation using an optical microscope, the circumference and longest diameter of the second phase particles can also be calculated using an SEM (scanning electron microscope). In the case of an SEM, the distinction between the second phase particles and the matrix can be achieved by the depth of the contrast in the COMP image (component image). Particles with a contrast deeper or lighter than the matrix are identified as second phase particles. A FlexSEM100 (scanning electron microscope, operating version 1.9) manufactured by Hitachi was used, with an acceleration voltage of 15 kV, a magnification of 1000 times, a scanning resolution of 1024 pixels, a scanning dwell time of 35 μs, and a field of view of 0.07 mm 2 SEM observation was performed under the above conditions. Then, the circumference of the second phase particles (mm / mm) was calculated using image analysis software (trade name: Image Analysis Software A Image, manufactured by Asahi Kasei Engineering Corporation). 2 ) and the longest diameter. When using SEM, the perimeter and the longest diameter of the second phase particles can be calculated in combination with image analysis software. The image analysis software uses AZtec (Ver.3.3SPI) manufactured by Oxford, and analyzes the second phase particles with a contrast deeper or lighter than the matrix one by one through EDS (energy dispersive X-ray analysis) to calculate the perimeter of the second phase particles (mm / mm 2The EDS analysis time for each detected second phase particle was 2 seconds.

[0036] The bottom plate is formed of an aluminum alloy, preferably an aluminum alloy in which the total content of Fe (iron), Mn (manganese) and Ni (nickel) is 0.05 mass % or more and 7.0 mass % or less, and the balance is aluminum and inevitable impurities. The aluminum alloy may arbitrarily further contain Si (silicon): more than 0 mass % and less than 24.0 mass %, Zn (zinc): more than 0 mass % and less than 7.0 mass %, Cu (copper): more than 0 mass % and less than 5.0 mass %, Mg (magnesium): more than 0 mass % and less than 3.5 mass %, Be (beryllium): more than 0 mass % and less than 0.0015 mass %, Cr (chromium): more than 0 mass % and less than 0.30 mass %, Zr (zirconium): more than 0 mass % and less than 0.15 mass %, Sr (strontium): more than 0 mass % and less than 0.1 mass %, Na (sodium): more than 0 mass % and less than 0.1 mass %, and P (phosphorus): more than 0 mass % and less than 0.1 mass %, and preferably the total content of Ti (titanium), B (boron) and V (vanadium) is more than 0 mass % and less than 0.500 mass %.

[0037] (Iron, Manganese, Nickel)

[0038] Fe exists mainly in the form of second phase particles (Al-Fe intermetallic compounds, etc.), and partially exists in the form of solid solution in the matrix. Through the formation of second phase particles and solid solution in the matrix, Fe has the effect of improving the impact resistance of the base plate. Mn and Ni also exist mainly in the form of second phase particles (Al-Mn intermetallic compounds, Al-Ni intermetallic compounds, etc.), and partially exist in the form of solid solution in the matrix. Through the formation of second phase particles and solid solution in the matrix, Mn and Ni also have the effect of improving the impact resistance of the base plate. However, when the total content of Fe, Mn and Ni is less than 0.05 mass%, the formation of second phase particles is insufficient, and the impact resistance may be reduced. On the other hand, if the total content of Fe, Mn and Ni exceeds 7.0 mass%, coarse second phase particles will be generated, and the impact resistance may be reduced. Therefore, the total content of Fe, Mn and Ni is preferably 0.05 mass% or more and 7.0 mass% or less.

[0039] (silicon)

[0040] When the aluminum alloy contains Si, Si mainly exists in the form of second phase particles (Si particles, etc.), which has the effect of improving the impact resistance of the base plate. Therefore, 24.0% by mass or less of Si can be arbitrarily added to the aluminum alloy. By making the Si content in the aluminum alloy less than 24.0% by mass, the generation of coarse Si particles is suppressed. As a result, the effect of further improving the impact resistance of the base plate can be obtained. When the aluminum alloy contains Si, the Si content is preferably 5.0% by mass or more to promote the formation of second phase particles and give full play to the effect of improving impact resistance.

[0041] (Zinc)

[0042] When the aluminum alloy contains Zn, Zn and other added elements form second phase particles, which has the effect of improving the impact resistance of the base plate. Therefore, 7.0% by mass or less of Zn can be added to the aluminum alloy. By making the content of Zn in the aluminum alloy 7.0% by mass or less, the generation of coarse second phase particles is suppressed. As a result, the impact resistance of the base plate can be further improved.

[0043] (copper)

[0044] When the aluminum alloy contains Cu, Cu mainly exists in the form of second phase particles (Al-Cu intermetallic compounds, etc.), which has the effect of improving the impact resistance of the base plate. Therefore, 5.0% by mass or less of Cu can be added to the aluminum alloy at will. By making the Cu content in the aluminum alloy 5.0% by mass or less, the generation of coarse second phase particles is suppressed. As a result, the impact resistance of the base plate can be further improved.

[0045] (magnesium)

[0046] When the aluminum alloy contains Mg, Mg and other added elements form second phase particles, which has the effect of improving the impact resistance of the base plate. Therefore, 3.5% by mass or less of Mg can be added to the aluminum alloy. By making the Mg content in the aluminum alloy 3.5% by mass or less, the generation of coarse second phase particles is suppressed. As a result, the impact resistance of the base plate can be further improved.

[0047] (beryllium)

[0048] When the aluminum alloy contains Be, Be is preferentially oxidized when the metal is molten, so the oxidation of other added elements can be suppressed, that is, other added elements become easy to form second phase particles, which has the effect of further improving the impact resistance of the bottom plate. Therefore, 0.0015 mass% or less of Be can be added to the aluminum alloy. However, even if more than 0.0015 mass% of Be is contained, the effect will be saturated, and no more significant improvement effect can be obtained.

[0049] (chromium)

[0050] When aluminum alloy contains Cr, Cr mainly exists in the form of second phase particles (Al-Cr intermetallic compounds, etc.), which has the effect of improving the impact resistance of the base plate. Therefore, 0.30% by mass or less of Cr can be added to the aluminum alloy. By making the Cr content in the aluminum alloy 0.30% by mass or less, the generation of coarse second phase particles is suppressed. As a result, the impact resistance of the base plate can be further improved.

[0051] (zirconium)

[0052] When the aluminum alloy contains Zr, Zr mainly exists in the form of second phase particles (Al-Zr intermetallic compounds, etc.), which has the effect of improving the impact resistance of the base plate. Therefore, Zr can be added to the aluminum alloy at any amount of 0.15% by mass or less. By making the Zr content in the aluminum alloy 0.15% by mass or less, the generation of coarse second phase particles is suppressed. As a result, the impact resistance of the base plate can be further improved.

[0053] (Sodium, Strontium, Phosphorus)

[0054] When the aluminum alloy contains at least one element of Na, Sr and P, Na, Sr and P have the effect of reducing the unevenness of the size of the second phase particles (mainly Si particles) in the base plate and reducing the uneven impact resistance of the base plate. Therefore, one or more elements selected from the group consisting of 0.1% by mass or less of Na, 0.1% by mass or less of Sr and 0.1% by mass or less of P can be added to the aluminum alloy. However, even if the contents of Na, Sr and P exceed 0.1% by mass respectively, the effects will be saturated and no more significant improvement effect can be obtained.

[0055] (titanium, boron, vanadium)

[0056] When the aluminum alloy contains at least one element of Ti, B and V, Ti, B and V have the effect of reducing the unevenness of the size of the second phase particles in the base plate and reducing the unevenness of the impact resistance of the base plate. Therefore, when at least one element of Ti, B and V is added, the total content of Ti, B and V is preferably in the range of 0.500 mass % or less. However, even if the total content of Ti, B and V exceeds 0.500 mass %, the effect is saturated and no more significant improvement effect can be obtained.

[0057] (Unavoidable impurities and other elements)

[0058] The bottom plate made of aluminum alloy may also contain elements other than the above-mentioned components, which are inevitable impurities. As these elements, Ga, Ca, etc. can be cited. As long as their content is below 0.10 mass % for each element and below 0.30 mass % for the total, the effect of the present invention will not be damaged.

[0059] (Thickness of the base plate)

[0060] The thickness of the bottom plate is preferably 0.5 mm or more and 2.0 mm or less. If the thickness of the bottom plate is less than 0.5 mm, the bottom plate may be deformed when it is dropped during the installation of the HDD. In addition, if the thickness of the bottom plate is greater than 2.0 mm, the number of disks that can be mounted in the HDD is reduced, so it is not preferred. Therefore, the thickness of the bottom plate is preferably 0.5 mm or more and 2.0 mm or less, and more preferably 0.5 mm or more and 1.5 mm or less.

[0061] Regarding the thickness of the base plate, Figure 4 As shown, the thickness of the bottom plate 10 is measured at any position in the area on one side of the disk, i.e., the filling area, in the area surrounded by the radius r25mm to the radius r30mm from the center C of the disk, and the measured value is defined as the thickness of the bottom plate 10. The thickness of the bottom plate 10 in this area is relatively thin, which affects the deformation of the bottom plate, so the above-mentioned effect can be exerted by controlling the thickness of the bottom plate 10 in this area. The thickness of the bottom plate 10 is measured using a micrometer, for example.

[0062] B. Method for manufacturing aluminum alloy bottom plate

[0063] The base plate can generally be manufactured by common methods such as die casting and casting. When making the base plate, the aluminum alloy substrate as the raw material is melted to make molten metal, and then the molten metal is made into the shape of the base plate by die casting or casting. In the production and casting process of the molten metal, when the molten metal is kept cast, the time for which the molten metal temperature is kept in the range of 550 to 700°C is preferably 0.1 to 1 hour. By keeping the temperature in the range of 550 to 700°C for 0.1 to 1 hour, the generation of coarse second phase particles can be suppressed, and a large amount of fine second phase particles can be generated. Therefore, the circumference of the second phase particles becomes larger, which has the effect of improving the impact resistance of the base plate.

[0064] C.Disk

[0065] The base material of disk is not particularly limited, for example, preferably a base material made of aluminum alloy or glass. In addition, the thickness of disk is preferably more than 0.20mm and less than 0.58mm, more preferably less than 0.48mm. If the thickness of disk is less than 0.20mm, then when the disk falls during the installation of HDD, the disk may be deformed or broken. On the other hand, if the thickness of disk is greater than 0.58mm, although the impact resistance is improved, the number of disks that can be carried in the HDD is reduced, so it is not ideal to promote the thinning of disk. It should be noted that disk can be made using disk substrates such as aluminum alloy substrates and glass substrates.

[0066] As the magnetic disk substrate, for example, an aluminum alloy substrate made of an aluminum alloy can be used. Hereinafter, the alloy composition of the magnetic disk aluminum alloy substrate and the method for producing the same will be described in detail.

[0067] (Alloy composition of aluminum alloy)

[0068] The aluminum alloy used for the aluminum alloy substrate for magnetic disk preferably contains elements such as Mg, Cu, Zn, Cr, etc. In addition, it may contain elements such as Fe, Mn, Ni, etc. which can improve rigidity.

[0069] Specifically, in one embodiment, the aluminum alloy used for the aluminum alloy substrate contains Mg as an essential element in an amount of not less than 1.0 mass % and not more than 6.5 mass %, and further arbitrarily contains Cu: not less than 0 mass % and not more than 0.070 mass %, Zn: not less than 0 mass % and not more than 0.60 mass %, Fe: not less than 0 mass % and not more than 0.50 mass %, Si: not less than 0 mass % and not more than 0.50 mass %, Cr: not less than 0 mass % and not more than 0.20 mass %, Mn: not less than 0 mass % and not more than 0.50 mass %, Zr: not less than 0 mass % and not more than 0.20 mass %, Be: not less than 0 mass % and not more than 0.0020 mass %, and the balance is composed of aluminum and unavoidable impurities.

[0070] In addition, in another embodiment, the aluminum alloy for the aluminum alloy substrate contains Fe as an essential element and one or two of Mn and Ni as optional elements. The total content of Fe, Mn, and Ni is 1.0% by mass or more and 7.0% by mass or less. Further, Si: 0% by mass or more and 14.0% by mass or less, Zn: 0% by mass or more and 0.7% by mass or less, Cu: 0% by mass or more and 1.0% by mass or less, Mg: 0% by mass or more and 4.5% by mass or less, Cr: 0% by mass or more and 0.30% by mass or less, Zr: 0% by mass or more and 0.20% by mass or less, Be: 0% by mass or more and 0.0015% by mass or less, Sr: 0% by mass or more and 0.1% by mass or less, Na: 0% by mass or more and 0.1% by mass or less, P: 0% by mass or more and 0.1% by mass or less may be optionally contained. The balance is composed of aluminum and inevitable impurities.

[0071] In the aluminum alloy for the aluminum alloy substrate, elements other than the above essential components and optional components may also be contained, and these elements are inevitable impurities. Examples of these elements include Ti, V, Ga, etc. The content of each element is 0.10% by mass or less, and the total is 0.30% by mass or less. In addition, Si may be actively added as an optional component, but sometimes it is not added. Si as an inevitable impurity is contained not only in raw material metals of general purity (Japanese: degane) but also in high-purity raw material metals with an Al purity of 99.9% or more. Thus, when Si is contained as an inevitable impurity, the content of Si is preferably 0.10% by mass or less.

[0072] (Method for manufacturing an aluminum substrate for a disk)

[0073] Hereinafter, an example of each process and process conditions of the manufacturing process of the aluminum alloy substrate for a disk will be described.

[0074] First, a molten metal of an aluminum alloy billet having the above-mentioned composition is prepared by heating and melting according to a conventional method. Next, the molten metal of the prepared aluminum alloy billet is cast by a semi-continuous casting (DC casting) method, a continuous casting (CC casting) method, etc. to cast an aluminum alloy billet. For the aluminum alloy ingot obtained by DC casting, a homogenization treatment is performed as needed. Next, the aluminum alloy ingot (DC casting) that has been homogenized or not homogenized is hot rolled to form a plate. Next, the hot-rolled rolled plate or the cast plate cast by the CC casting method is cold rolled to form an aluminum alloy plate. Before cold rolling or in the middle of cold rolling, annealing treatment may also be performed to ensure cold rolling workability. Next, the aluminum alloy plate obtained by cold rolling is punched into a ring shape to form a ring-shaped aluminum alloy plate. The ring-shaped aluminum alloy plate is flattened by pressurization to become a disc blank. Before zinc dipping treatment, etc., the disc blank is subjected to cutting and grinding and heating treatment as needed. Next, the surface of the disk blank is degreased and etched, and then zinc treatment (Zn replacement treatment) is performed. In the zinc treatment, a zinc film is formed on the surface of the disk blank. Furthermore, as a base treatment for the magnetic body to adhere, the surface of the disk blank treated with zinc is subjected to electroless Ni-P plating. The plated surface after the electroless Ni-P plating treatment is polished to make it smooth. In this way, the aluminum substrate for magnetic disks is manufactured by polishing the surface after the plating treatment.

[0075] (Glass substrate for magnetic disk)

[0076] For example, a glass substrate made of a glass material may be used as the magnetic disk substrate. Hereinafter, the applicable glass material and the manufacturing method of the glass substrate will be described in detail with respect to the magnetic disk glass substrate.

[0077] (Glass material)

[0078] The glass used for the magnetic disk substrate is known to include the following glass: 2 : 55 mass % or more and 75 mass % or less as the main component, and further containing Al 2 O 3 : 0.7 mass % or more and 25 mass % or less, Li 2 O: 0.01 mass% or more and 6 mass% or less, Na 2 O: 0.7 mass % or more and 12 mass % or less, K 2 O: 0 mass% to 8 mass%, MgO: 0 mass% to 7 mass%, CaO: 0 mass% to 10 mass%, ZrO 2 : 0 mass % or more and 10 mass % or less, TiO 2: 0 mass % or more and 1 mass % or less. Such glass may further contain: B 2 O 3 (It is contained as an essential component in aluminoborosilicate glass and borosilicate glass), which reduces viscosity and improves solubility and clarity; SrO and BaO, which reduce high-temperature viscosity, improve solubility, clarity and formability, and show an effect of improving Young's modulus; ZnO, which improves ion exchange performance and reduces high-temperature viscosity without reducing low-temperature viscosity; SnO 2 , which improves clarity and ion exchange performance; Fe 2 O 3 , which is a coloring agent; etc., in addition, it may also contain As as a clarifier 2 O 3 , Sb 2 O 3 In addition, oxides of La, P, Ce, Sb, Hf, Rb, Y, etc. may be contained as trace elements.

[0079] (Method for manufacturing glass substrate for magnetic disk)

[0080] Next, an example of a method for producing a magnetic disk glass substrate will be described.

[0081] First, melt the glass blank prepared according to the specified chemical composition, and extrude the molten block from both sides by direct extrusion to make a glass original plate with a desired thickness. The production of the glass original plate is not limited to the direct extrusion method, and can also be a float method, a fusion method, a re-drawing method, etc. Next, the glass original plate is cored to form a ring shape, and then the inner diameter and the outer diameter are polished to make a ring-shaped glass plate with a desired inner diameter size, outer diameter size, and chamfer length. Then, the surface of both sides of the ring-shaped glass plate is ground (hereinafter referred to as lapping) by a grinding machine to make a ring-shaped glass substrate with a desired plate thickness and flatness. Furthermore, the surface of both sides of the ring-shaped glass substrate is polished by a polishing machine to make a disk of the desired thickness, that is, a glass substrate. In the middle of the polishing process, a chemical strengthening treatment using a sodium nitrate solution, a potassium nitrate solution, etc. can be implemented. In this way, a glass substrate for a magnetic disk is manufactured by surface polishing.

[0082] (Other structures)

[0083] In addition to the aluminum alloy substrate for magnetic disk or the glass substrate for magnetic disk, the magnetic disk may also have a magnetic layer stacked on these substrates. Furthermore, it may also have a protective layer stacked on the magnetic layer made of carbon materials such as diamond-like carbon and a lubricating layer coated on the protective layer made of lubricating oil.

[0084] As mentioned above, the hard disk drive built in a thin substrate and the bottom plate member for the hard disk drive built in a thin substrate according to the present embodiment have been described. However, the present invention is not limited to the above-mentioned embodiment, and various modifications and changes can be made based on the technical concept of the present invention.

[0085] Example

[0086] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples unless it exceeds the gist of the present invention.

[0087] <Production of Aluminum Alloy Floor Member>

[0088] Aluminum alloy floor members for evaluation in Examples and Comparative Examples were produced by the following method.

[0089] For each of the Examples and Comparative Examples, a molten metal having the chemical composition shown in Table 1 was prepared in a melting furnace / heat-holding furnace. Next, a bottom plate member (test material) having a thickness of 1.5 mm was produced by supplying the molten metal in the melting furnace / heat-holding furnace to a mold. The time for which the molten metal temperature was maintained in the range of 550 to 700° C. is shown in Table 1.

[0090] The following describes a method for measuring the circumference and the longest diameter of the second phase particles of each test material and a method for evaluating the impact resistance.

[0091] <Method for measuring the circumference and longest diameter of second phase particles>

[0092] After the surface of the bottom plate member was polished, an optical microscope was used without using a polarizing filter to analyze the surface of the bottom plate member at 400 times the magnification within the range of 0.07 mm. 2 The above fields of view were observed, and the circumference of the second phase particles (mm / mm) was measured using image analysis software (trade name: Image Analysis Software A-image-kun, manufactured by Asahi Kasei Engineering Corporation) 2 ) and the longest diameter. The distinction between the second phase particles and the matrix is ​​achieved by the depth of contrast in the image taken with an optical microscope, and the particles with a deeper or lighter contrast than the matrix are regarded as second phase particles. It should be noted that when the bottom plate is used for measurement, Figure 4 The surface was polished and measured at an arbitrary position in the area on one side of the disk, that is, in the filling area, in the area surrounded by the radius r25 mm to the radius r30 mm from the center C of the disk.

[0093] Table 1

[0094]

[0095] As shown in Table 1, in the test materials of Examples 1 to 4, the circumference of the second phase particles with the longest diameter of 10 μm or more exposed on the surface of the test material is 3 mm / mm.2 The number of second phase particles with a maximum diameter of 500 μm or more is 0 / mm 2 .like Figure 2 As shown in the figure, as long as the circumference of the second phase particles with the longest diameter of 10μm or more in the metallographic structure of the bottom plate is 3mm / mm 2 The above can be evaluated as being able to reduce the impact transmitted to the disk. Figure 2 , it can be evaluated that these test materials can improve the impact resistance of the magnetic disk.

[0096] On the other hand, for the test material of Comparative Example 1, the molten metal temperature was kept in the range of 550-700°C for 1.5 hours, and many second phase particles with a maximum diameter of 500 μm or more were generated. Therefore, the number of second phase particles with a maximum diameter of 500 μm or more was 1 / mm. 2 , the test material is not suitable as a base plate component.

[0097] In addition, for the test material of Comparative Example 2, the circumference of the second phase particles is 1.6 mm / mm 2 , because it is too short, so quoted Figure 2 , it can be evaluated that the impact resistance characteristics of this test material are inferior to those of the bottom plate members produced from each test material of Examples 1 to 4.

[0098] Explanation of symbols

[0099] 1. A hard disk drive (HDD) built into a thin substrate; 10. A bottom plate; 20. A spindle motor; 30. A magnetic disk; 40. An actuator; 50. A magnetic head; 60. A cover plate; 70. A swing arm.

Claims

1. A thin substrate with a built-in hard disk drive, characterized in that: include: A disk-shaped magnetic disk having a through hole in the center; a spindle motor inserted into the through hole of the magnetic disk and supporting the magnetic disk in a manner that allows co-rotation; and a base plate made of aluminum alloy, which is used to support the spindle motor, the base plate having a metallographic structure, in which the perimeter of the second phase particles with the longest diameter of 10 μm or more is 3 mm / mm 2 and the number of second phase particles with the longest diameter of 500 μm or more is 0 / mm 2 .

2. The thin substrate built-in hard disk drive according to claim 1, characterized in that: The bottom plate has a thickness of 0.5 mm or more and 2.0 mm or less.

3. A bottom plate member for a thin substrate built-in hard disk drive and made of aluminum alloy, characterized in that: The bottom plate member has a metallographic structure, and the circumference of the second phase particles having the longest diameter of 10 μm or more in the metallographic structure is 3 mm / mm 2 and the number of second phase particles with the longest diameter of 500 μm or more is 0 / mm 2 .

4. The base member according to claim 3, wherein: The bottom plate member has a thickness of 0.5 mm or more and 2.0 mm or less.

Citation Information

Patent Citations

  • Aluminum alloy substrate for magnetic disk

    WO2016068293A1

  • Substrate for magnetic disk

    CN108368568A

  • Aluminum alloy substrate for magnetic disks, method for producing same, and magnetic disk using said aluminum alloy substrate for magnetic disks

    CN111164228A